Peacekeeping or Perpetuating Insecurity? Human Security Implications of Peacekeeping Missions in South Sudan - Kester C. Onor; Jennifer C. Ndulue (PERSPEKTIF, 2026)
Peacekeeping missions (PKMs) are widely promoted as instruments of civilian protection and post-conflict stabilisation, yet their human security outcomes remain contested, particularly in fragile states. In South Sudan, sustained peacekeeping engagement since 2013 has coincided with protracted political rivalry and ethnic fragmentation, raising questions about the effectiveness of such interventions in improving everyday human security. This study examines the human security implications of peacekeeping missions in South Sudan between 2013 and 2021, focusing on their interactions with civilian protection, displacement, and community-level vulnerabilities. Anchored in the Fiduciary Theory of Humanitarian Intervention, which emphasises the ethical obligation of interveners to prioritise civilian welfare alongside operational security, the study adopts a qualitative, descriptive, and exploratory design. Data are drawn from academic literature, United Nations and humanitarian agency reports, policy documents, and credible media sources, and are analysed thematically. The findings reveal that while peacekeeping missions have provided limited protective functions, they have struggled to reduce violence or address broader human security threats significantly. Protection of Civilians (PoC) sites offered temporary refuge but were undermined by governance deficits, resource constraints, abuse allegations, health risks, and the circulation of small arms. Moreover, peacekeeping efforts prioritised elite political settlements over community-based reconciliation, limiting their capacity to address structural drivers of insecurity. The study concludes that peacekeeping in South Sudan functioned essentially as crisis management rather than a transformative human security intervention, underscoring the need for a recalibration towards inclusive peacebuilding and community-centred security.